2020
DOI: 10.1128/mbio.00901-20
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulations of Stressed Yersinia pseudotuberculosis Preferentially Survive Doxycycline Treatment within Host Tissues

Abstract: Severe systemic bacterial infections result in colonization of deep tissues, which can be very difficult to eliminate with antibiotics. It remains unclear if this is because antibiotics are not reaching inhibitory concentrations within tissues, if subsets of bacteria are less susceptible to antibiotics, or if both contribute to limited treatment efficacy. To detect exposure to doxycycline (Dox) present in deep tissues following treatment, we generated a fluorescent transcriptional reporter derived from the tet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…Recently, we have shown that NO-exposed Hmp + cells preferentially survive doxycycline treatment in our mouse model of infection, which suggested the Hmp + cells may represent a slow growing subpopulation of bacteria [30]. Our in vitro results were consistent with this, where exposure to NO was sufficient for DsRed 42 signal accumulation.…”
Section: Plos Pathogenssupporting
confidence: 88%
See 3 more Smart Citations
“…Recently, we have shown that NO-exposed Hmp + cells preferentially survive doxycycline treatment in our mouse model of infection, which suggested the Hmp + cells may represent a slow growing subpopulation of bacteria [30]. Our in vitro results were consistent with this, where exposure to NO was sufficient for DsRed 42 signal accumulation.…”
Section: Plos Pathogenssupporting
confidence: 88%
“…It remains unclear if the protective expression of hmp by peripheral cells comes at a fitness cost, and if this stress promotes the formation of a slow-growing subset of bacteria at the periphery of microcolonies. The preferential survival of hmp-expressing cells during antibiotic treatment supported this hypothesis [30], however our results here will suggest that NO exposure occurs transiently within host tissues, and that Hmp + cells retain the ability to divide.…”
Section: Plos Pathogenssupporting
confidence: 62%
See 2 more Smart Citations
“…Studies with Yptb have uncovered a great deal of knowledge about the interactions that occur at the host-bacterial interface. Some examples of key findings with Yptb include the discovery of invasin, an adhesin that promotes entry into host cells (Isberg, Voorhis, & Falkow, 1987); novel findings with siderophores and iron acquisition systems within host tissues (Pieper et al, 2010;Schwiesow et al, 2018); elucidation of the structure and function of the type III secretion system (T3SS) and its associated effector proteins and the impact of these effector proteins on the host cell cytoplasm and signaling pathways (Peterson et al, 2017;Rolán, Durand, & Mecsas, 2013;Schesser et al, 1998;Songsungthong, Higgins, Rolán, Murphy, & Mecsas, 2010;Spinner et al, 2010;Zhang & Bliska, 2010); definition of key events in the evolution of pathogens through genetic comparisons between Yptb and Y. pestis (Achtman et al, 1999;Chain et al, 2004); definition of the extent of heterogeneity within bacterial populations replicating in host tissues and identification of examples of cooperative behavior (Davis et al, 2015;Nuss et al, 2016;Raneses, Ellison, Liu, & Davis, 2020); determination of the role of dendritic cells and monocytes in promoting adaptive immune responses within intestinal tissues and the long-term impact on protective memory responses within white adipose tissue (Han et al, 2017;Zhang, Khairallah, Sheridan, van der Velden, & Bliska, 2018;Zhang, Mena, Romanov, & Bliska, 2014); and findings from the aforementioned studies of temperature-dependent regulation of virulence factor expression (Herbst et al, 2009;Nuss et al, 2016;Portnoy, Moseley, & Falkow, 1981).…”
Section: Commentary Background Informationmentioning
confidence: 99%